An approximation between Skinner and Bakhtin for the study of language (Brazilian Journal of Behavioral and Cognitive Therapy, 2007)
The goal of this paper was to accomplish an approximation between two authors – M.M.Bakhtin and B.F.Skinner – from two different fields of knowledge – the first of them from the sciences of language, the second, from psychology – for the study of language. Starting with the analysis of the most important texts related to the issue of language of each of the two authors, some aspects were selected for the comparison of the way they propose to deal with language. The identification of similarities between the two authors points out to the possibility of considering the contribution of both of them for the understanding of language. And based on some of the differences between them it is possible to devise ways to enlarge this understanding.